Effects of botulinum toxin A and/or bimanual task-oriented therapy on upper extremity impairments in unilateral Cerebral Palsy: An explorative study. (May 2015) - Speth, Lucianne; Janssen-Potten, Yvonne; Leffers, Pieter; Rameckers, Eugene; Defesche, Anke; Winkens, Bjorn; Becher, Jules; Smeets, Rob; Vles, J.S.H.
Abstract Objective This study reports on the effects of botulinum toxin A (BoNT-A) injections in the upper extremity (UE) of children with unilateral Cerebral Palsy (uCP) combined with bimanual task oriented therapy (BITT) or either treatment modality performed separately on UE range of motion (ROM), spasticity and (functional) strength. Methods Thirty-five children, mean age 7.14 years (SD 2.63) of whom 11 had a Manual Ability Classification Score (MACS) I, 15 MACS II and 9 MACS III, participated. The trial started with four study groups: BoNT-A-only (n = 5), BITT-only (n = 11), BoNT-A + BITT (n = 13), and control (n = 6). Twenty-two children were randomized and, due to recruitment problems 13 children received their parents' preferred treatment: BoNT-A + BITT or BITT-only. Three comparisons were analysed: BITT (BoNT-A + BITT and BITT-only; n = 24) versus no BITT (BoNT-A-only and control; n = 11), BoNT-A (BoNT-A-only and BoNT-A + BITT; n = 18) versus no BoNT-A (BITT-only and control; n = 17), and the additional effect of BoNT-A (BoNT-A + BITT versus BITT-only). Results BoNT-A significantly decreased key grip strength and finger flexion tone, had a clinically relevant (additional) positive effect on active thumb abduction and supination and a significantly negative effect on unilateral functional strength. BITT + BoNT-A significantly increased active supination. BITT reduced elbow flexor tone and BITT-only resulted in more improvement than BoNT-A + BITT in functional unimanual and, to a lesser extent, in bimanual grip strength. Conclusions In comparison with BoNT-A + BITT, BITT-only gives more improvement on functional grip strength and, therefore, could possibly increase bimanual performance. In this case, the (additional) role of BoNT-A may be an increase in active supination and thumb abduction.